Attitudes and Barriers of Primary School Children on Cardiopulmonary Resuscitation for Drowning Victims - Nurumal, Mohd. Said; Shamsudin, Luqman Aqiel; Jamaludin, Thandar Soe Sumaiyah; Ramli, Muhammad Zahir (Universitas Pendidikan Indonesia, 2021)
Introduction:Â Cardiopulmonary Resuscitation is a lifesaving procedure whenever a cardiac arrest victim. Drowning is also one of the factors that can lead to cardiac arrest, especially in coastal areas. Children who live in the coastal community are very at risk for drowning due to the nature of their playground located in the coastal zone. Empowering and educating them to skill onÂ Cardiopulmonary Resuscitation (CPR) is more important. To provide effective prevention means in reducing the mortality rate, it would require attitudes and barriers from the public especially.Â Objectives:Â Â This study aimed to explore attitudes and barriers to CPR in drowning victims for primary school children aged in the coastal community of Malaysia.Â Method:Â This study follows a quasi-experimental design using the pre-and post-intervention with educational videos about CPR. The studied participants were participated in this study through an online google form survey due to the current pandemic situation. All the participants were from primary school children in the coastal area.Â Results:Â This study revealed that most of the participants (70.6%) would perform CPR for drowning victims after the intervention given to them compared to pre-intervention, which was 58.8%. As for the â€œDoes the public need to learn CPR?â€, most of the participants (88.2%) agreed that everyone needed to learn CPR procedures after giving the intervention. 76.5% of the participant want training on CPR for drowning before the intervention, but there is a slight decrease after intervention given, which is (64.7%). Around 58.8% of the participants were confident in initiating CPR for drowning victims before and after the intervention. Moreover, approximately 82.4% of the participant would perform CPR if their friends were in danger after the intervention. The majority of the participants (70.6%) thinks adults are more suitable to perform CPR in the post-intervention questionnaire compared to only 52.9% for the pre-intervention questionnaire.Â Â Conclusion: Primary school children showed a significant change in their attitudes and barriers after receiving the intervention. Consideration should be given to integrating the CPR training or lesson in the syllabus of primary education would save more lives.Â AbstrakÂ Pendahuluan: Resusitasi Jantung Paru merupakan tindakan penyelamatan jiwa pada korban henti jantung. Tenggelam juga merupakan salah satu faktor yang dapat menyebabkan serangan jantung, terutama di daerah pesisir. Anak-anak yang tinggal di masyarakat pesisir sangat berisiko tenggelam karena karakteristik taman bermainnya yang berada di wilayah pesisir. Memberdayakan dan mendidik mereka untuk keterampilan Resusitasi Jantung Paru (RJP) sangat penting untuk memberikan sarana pencegahan yang efektif dalam menurunkan angka kematian, maka diperlukan sikap dan hambatan dari masyarakat khususnya. Tujuan: Penelitian ini bertujuan untuk mengetahui sikap dan hambatan CPR pada korban tenggelam pada anak usia sekolah dasar di masyarakat pesisir Malaysia. Metode: Penelitian ini mengikuti desain quasi-experimental dengan menggunakan pre-and post-intervention dengan video edukasi tentang CPR. Partisipan yang diteliti diikutsertakan dalam penelitian ini melalui survei online google form karena situasi pandemi saat ini. Semua peserta berasal dari anak-anak sekolah dasar di wilayah pesisir. Hasil: Penelitian ini mengungkapkan bahwa sebagian besar partisipan (70,6%) akan melakukan CPR pada korban tenggelam setelah diberikan intervensi dibandingkan dengan sebelum intervensi yaitu 58,8%. Untuk pertanyaan â€œApakah masyarakat perlu mempelajari CPR?â€, sebagian besar peserta (88,2%) setuju bahwa setiap orang perlu mempelajari prosedur CPR setelah memberikan intervensi. 76,5% peserta menginginkan pelatihan CPR untuk tenggelam sebelum intervensi, namun ada sedikit penurunan setelah intervensi diberikan, yaitu (64,7%). Sekitar 58,8% dari peserta yakin dalam memulai CPR untuk korban tenggelam sebelum dan sesudah intervensi. Selain itu, sekitar 82,4% peserta akan melakukan CPR jika teman mereka dalam bahaya setelah intervensi. Mayoritas peserta (70,6%) berpikir orang dewasa lebih cocok untuk melakukan CPR dalam kuesioner pasca-intervensi dibandingkan dengan hanya 52,9% untuk kuesioner pra-intervensi. Kesimpulan: Anak sekolah dasar menunjukkan perubahan sikap dan hambatan yang signifikan setelah menerima intervensi. Pertimbangan harus diberikan untuk mengintegrasikan pelatihan atau pelajaran CPR dalam silabus pendidikan dasar akan menyelamatkan lebih banyak nyawa.